Alignment of marketing and business strategies with the financial performance of organizations - Mazyar Ganjoo; Sohrab Khalili Shavereini; Mahmood Alborzi; Seyed Mohammad Zargar (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: The alignment of marketing and business strategy and their relationship with the organization’s financial performance are research domains which are still investigated despite having a long history. This is due to the different aspects of the topic and the different results in various organizational contexts and time periods. Although marketing and business plans are similar, there are differences between their characteristics. The present study attempted to analyze the relationship between the alignment of marketing and business strategies with the organization’s financial performance in a five-year period from 2014 to 2018 in a group of companies registered in Tehran Stock Exchange.Methodology: The configuration theory in strategic management was used to develop the conceptual model. The marketing strategy was divided into the configurations of aggressive, mass, minimizer, and value-related, and the business strategy was divided into the four configurations of prospector, low cost defenders, differentiated defenders, and analyzers. Research hypotheses involved the relationship between the combination of configurations and the organization’s financial performance. One of the well-known tools for identifying marketing strategy is the self-typing paragraph approach. The Miles framework was used to identify the business strategy. To measure the performance, a questionnaire was used with six factors including sales growth volume, market share status, net profit growth status per share, operating profit margin status, net profit margin, and P/E ratio. The list of the Iranian stock exchange companies was used to select the companies. These companies were filtered based on three conditions. The first condition was the existence of an independent marketing department in these companies, the second condition was the existence of a competitive or semi-competitive environment, and the third condition was the companies’ lack of a joint venture investor. Thus, 108 companies cooperated with the research. First, marketing and business strategies and organization’s financial performance were identified. Then, the companies were divided into two groups including aligned and non-aligned groups. After that, the mean test was used for the statistical comparison of the performance of the aligned and non-aligned states.Results and Discussion: As the results revealed, the mean performance of the aligned states significantly differed from that of the non-aligned states. In the field of marketing strategy, the post hoc test showed that the mean performance of the aggressive strategy was higher than in other strategies. The value-related and mass strategies had a higher mean performance than the minimizer strategies but were not different from each other. In the field of business strategy, the prospector strategy and the differentiated defenders had higher mean performances than the low-cost defenders and analyzer. In general, the statistical results rejected the equality of mean performance in different combinations of business and marketing strategy.According to the research findings, four bodies were identified. The first body was the combination of the low-cost defenders with the minimizer strategy. In this body, the company's main focus was on maintaining the market share. These businesses reduce their risks by delaying the introduction of the product in the market until the product is established by others in the market. Adequate quality, low price and very wide distribution strategy are pursued by them. They generally focus on the product line and use the least amount of professional marketing staff. The second body was the combination of the differentiated defenders with the value-related strategy. In this body, the ratio of operating profit to sales was high. Also, the integrated chain of communication with customers was active, and the company used a relatively conservative and somewhat risky approach to activities. The company paid only some attention to market share and focused on maintaining the market. The company paid attention to capacity building, as compared to its competitors, and implemented the market-product strategy. The company considered its marketing strategy combination to be innovative, and high-quality products and the main value were in close relationship with the customer. They conducted mediocre marketing research and generally demanded a fair price. Their distribution strategy was somewhat selective, and they used moderate advertisement. In fact, the focus was on customer orientation, and there was a tendency for niches markets. The Third body was the combination of the analyzers with the mass marketing strategy. In this body, the ratio of the operating profit to sales was high. Also, an integrated chain of communication with customers and suppliers was active, and the company used a relatively conservative view. The company paid some attention to market share and focused on maintaining the market. There was a lot of focus on market-product strategy, but serious attention was also paid to cost reduction. The company was dominated by the engineering-oriented view. An extensive data analysis was performed every day for optimal decision making and long-term planning. These businesses generally produce high-quality products that follow market innovation and use very wide distribution channels. The fourth body was the combination of the prospectors with the aggressive strategy. In this body, the operating profit margin was taken into consideration, the integrated chain of communication with the customers and suppliers was active, and the company used a very risky view. The company paid serious attention to the market share. It was a leader in terms of innovation, diversity and capacity development, compared to its competitors, and fully implements the market-product strategy. The development of new markets was a priority and the company had an entrepreneurial outlook. These businesses usually produce innovative and high-quality products, and have a very close relationship with the customer and conduct a very extensive marketing research. This research is done to identify and encourage market segments where buyers tend to pay high prices. Buyers in these markets are selected with a selective distribution strategy and are contacted with through intense and focused advertising.Conclusion: These results indicate the proximity of marketing and business strategies and the direct effect of marketing strategy on the organization’s performance. The research contributes to managers’ knowledge of successful and high-performance alignments. Therefore, organizations can intensify marketing activities and reinforce their alignment skills.